(untitled) (Harmoni, 2013)
A qualitative approach is used in this study. The focus lies women’s participation in making decisions on finance management in muslim families. This study emphasizes in the background of the equality between wife and husband’ decision in their home. The equality between wife and husband in domestic areas, especially in deciding family’s finance management is still complained. The facts showed women (wives) has not fully participated in deciding family’s finance management. The wives participated partially in deciding the small need of money, but not in big need of money